ISLAMIC BASED HIERARCHICAL CONSUMPTION: LITERATURE REVIEW IN CONVENTIONAL AND ISLAMIC CONTEXTS - Basri Abd.Ghani; Ahmad Azrin Adnan (Journal of Islamic, Social, Economics and Development, 2017)
This article aims to examine the position of the literatures on the Islamic-based hierarchical consumption (IBHC) in the field of Muslim consumer behavior (MCB) and conventional sphere. The elucidation on MCB is rather extensive in scope. Since IBHC is deemed to be the source for the MCB, how far do the literatures cover the IBHC? This paper attempts to address these issues based on secondary classical and contemporary sources. It thus formed an outline for the writings on IBHC in the literatures on MCB as a whole. As such, the literature gap and research justification on IBHC will surface.